Constrained controllability of nonlinear stochastic impulsive systems - Karthikeyan, Shanmugasundaram; Balachandran, Krishnan (Zielona Góra: Uniwersytet Zielonogórski)
This paper is concerned with complete controllability of a class of nonlinear stochastic systems involving impulsive effects in a finite time interval by means of controls whose initial and final values can be assigned in advance. The result is achieved by using a fixed-point argument.
Keywords: complete controllability; nonlinear stochastic system; impulsive effect; Banach contraction principle